Hubungan Antara Dukungan Sosial dan Tingkat Stres pada Pasien dengan Penyakit Kronis - Puput Mulyono; Kresna Agung Yudhianto (Inovasi Kesehatan Global, 2025)
Type 2 Diabetes Mellitus is a chronic disease that not only causes physical disorders, but also has an impact on the patient's psychological condition, especially increased stress levels. Unmanaged stress can worsen medical conditions, decrease adherence to treatment, and negatively impact the patient's quality of life. Social support is known to have an important role as a protective factor in helping patients cope with psychological burden. This study aimed to analyze the relationship between social support and stress levels in patients with Type 2 Diabetes Mellitus. The research design used was descriptive correlation with a cross-sectional approach, involving [number of respondents] patients selected with the [mention sampling technique]. The research instrument used a validated social support questionnaire and stress scale. The data were analyzed by the Pearson/Spearman correlation test according to the data distribution. The results showed that there was a significant relationship between social support and stress levels in patients with Type 2 Diabetes Mellitus (p < 0.05), with a negative correlation direction, which means that the higher the social support received by the patient, the lower the level of stress experienced. These findings confirm the importance of the role of family, health workers, and the social environment in supporting patients to manage stress and improve quality of life. This study recommends the need for social support-based interventions in diabetes management programs in health services.